THE EFFECT OF SELF-EFFICACY AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN EMPLOYEES EDUCATION AND CULTURE OFFICE SOUTH COAST DISTRICT - Rahmizal, Maizul; Dewi, Rika Sandra (LPPM Universitas Bina Bangsa, 2022)
The performance of employees in the Government is one of the determining factors in efforts to improve the quality of services to the community, it is necessary to give serious attention from various parties. This study aims to determine the effect of self-efficacy and job satisfaction on employee performance. The population of this study were employees in the Pesisir Selatan Regency Education and Culture Office as 60 people. The sample in this study was 60 people with the sampling technique used was saturated sampling. Therefore, the data analysis is the statistical analysis in the form of multiple linear regression tests. These results indicate that the variable self efficacy has a positive and significant effect on employee performance and variable job satisfaction has a positive and significant effect on employee performance